(untitled) (Bangladesh Journal of Urology, 2020)
Objective: This study was conducted to compare the outcome of anastomotic urethroplasty with that of traditional optical internal urethrotomy in the treatment of short-segment bulbar urethral stricture. Methods: This comparative clinical study was conducted in the Department of Urology, Dhaka Medical College Hospital over a period 1 year from January 2007 to December 2008. A total of 50 patients with short-segment (< 2 cm) bulbar urethral strictures were consecutively included in the study. The test statistics used to analyses the data were Fisher’s Exact Probability Test, Student’s t-Test. For all analytical tests, the level of significance was set at 0.05 and p < 0.05 was considered significant. Results: About one-quarter (24%) of patients in OI Urethrotomy group experienced bleeding, 4% epididymitis and another 4% incontinence. In contrast, 8% of patients in Anastomotic Urethroplasty group complained of periurethral leakage, 8% fever and another 8% wound infection. Apart from bleeding, all the complications were almost homogeneously distributed between groups.Six (24%) of patients in OI Urethrotomy Group exhibited narrow urinary stream at month 3, as opposed to none in Anastomotic Urethroplasty Group (p = 0.001). Nearly 30% of patients in OI Urethrotomy Group had narrow urinary stream at month 6 compared 4% in Anastomotic Urethroplasty Group (p = 0.024). Of the 25 patients in OI Urethrotomy Group, 1(4%) developed UTI at month 3 and 5(20%) at month 6. None of the patients in Anastomotic Urethropasty Group developed UTI. There was significant difference between groups in terms of UTI at month 6 (p = 0.025).The recurrence rate of stricture in OI Urethrotomy was 24% (6 out of 25 patients) at month 3. However, none in Anastomotic Urethroplasty Group had history of recurrence of stricture (p = 0.011). At baseline the mean uroflowmetry was 5.5 ml/sec in both groups which immediately increased to 25.3 ± 2.6 ml/sec and 23.9 ± 2.2 ml/sec in OI urethrotomy and Anastomotic Urethroplasty groups respectively and then dropped to 18.4 ± 6.3 ml/sec and 20.2 ± 2.6 ml/sec in OI Urethrotomy and Anastomotic Urethroplasty groups respectively at month 3 and to 17.8 ± 6.4 ml/sec and 19.6 ± 2.6 ml/sec respectively at month 6. Conclusion: This study concludes that Anastomotic Urethroplasty is an effective and satisfactory technique for the treatment of short-segment bulbar urethral stricture. Bangladesh Journal of Urology, Vol. 16, No. 1, Jan 2013 p.21-25